Self-Injury Using the Rational Emotive Behavior Therapy REBT Approach in Group Counseling for High School Students - Dedi Effendi; Yeni Karneli; Netrawati (Journal Of Psychology, Counseling And Education, 2025)
This research looks at the mechanism of Rational Emotive Behavior Therapy (REBT) and how effective it is in addressing Self-Injury behavior among high school students through group counseling. Using the literature review technique, this study evaluated articles, books, and previous research related to this topic. The results of the analysis showed that REBT has significant potential to improve emotion regulation skills in adolescents and reduce Self-Injury behavior. Students involved in group counseling with the REBT approach showed a significant increase in their ability to manage their negative emotions and self-esteem, as well as a significant decrease in the frequency of their Self-Injury behaviors. The influence of the social environment, such as peer group dynamics and family conditions, contributing to self-injury behavior, was the main concern of this study. It was found that students who experienced social pressure, such as bullying, had a greater tendency to engage in self-injury behaviors. In addition, there were significant gender differences in self-injury behaviors: female students more often used methods such as cutting, while male students tended to use more visible methods. This study suggests that a counseling program incorporating REBT is essential to create a safe and welcoming environment for students. By getting the right support from parents and counselors, it is expected that Self-Injury behavior will be less and adolescents' mental health will be better. The findings suggest that this method not only serves as a therapy but also helps adolescents' emotional development.